The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1063/1.3267044
|View full text |Cite
|
Sign up to set email alerts
|

Development and fertility studies on post-bio-electrosprayed Drosophila melanogaster embryos

Abstract: Bio-electrosprays (BESs) provide a means of precisely manipulating cells and thus have the potential for many clinical uses such as the generation of artificial tissuesorgans. Previously we tested the biological safety of this technology with a variety of living cells and also embryos from the vertebrate model organisms Danio rerio (zebrafish) and Xenopus tropicalis (frog). However, the viability and fertility of the treated embryos could not be fully assessed due to animal licensing laws. Here we assay the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It was observed that the method does not cause a significant reduction in mesenchymal stem cell viability, significant chromosomal alterations in mononuclear cells, alterations in the pluripotency of the embryonic stem cells or genetic and physical damage that can affect the development of multicellular organism. [7][8][9][10] Although these studies show that BES is a safe technique for cell processing, until now, no study has investigated if the time necessary for the realization of BES can have a negative effect on the cells. Regarding the association of BES with scaffold production techniques, the time parameter becomes an important factor for observation.…”
Section: Introductionmentioning
confidence: 98%
“…It was observed that the method does not cause a significant reduction in mesenchymal stem cell viability, significant chromosomal alterations in mononuclear cells, alterations in the pluripotency of the embryonic stem cells or genetic and physical damage that can affect the development of multicellular organism. [7][8][9][10] Although these studies show that BES is a safe technique for cell processing, until now, no study has investigated if the time necessary for the realization of BES can have a negative effect on the cells. Regarding the association of BES with scaffold production techniques, the time parameter becomes an important factor for observation.…”
Section: Introductionmentioning
confidence: 98%
“…Those studies have demonstrated post-treated cells are indistinguishable to those controls. In addition to these studies Jayasinghe and coworkers have assessed the processing of whole organisms for further investigating whether the processing physical stresses involved in combination with the high intensity electric field has any effects on cell rearrangement to embryological development [9][10][11][12]. Thus, elucidating no gross negative effects brought on the treated embryos in comparison to those controls.…”
Section: Introductionmentioning
confidence: 99%
“…The operational parameters are subsequently seen to enable control over droplet break‐up and its precision deposition. The technology has undergone complete biological and engineering studies, which have been applied for the handling of a wide range of cells and whole organisms at very early stages of development 12, 13. These biological investigative studies have been furthered by studies of post‐treated cells engrafted into living hosts (mice) that assess biological processes that may have been missed during in vitro studies.…”
Section: Non‐contact Jet‐based Direct‐cell Handling Approachesmentioning
confidence: 99%